Female Agency in the Song ‘Man I Need’ by Olivia Dean: A Systemic Functional Discourse Analysis - Amalia Agatha; Fariq Shiddiq Tasaufy (ELS Journal on Interdisciplinary Studies in Humanities, 2026)
Song lyrics, as a widely consumed form of popular discourse, play a significant role in constructing gender representations and power relations through specific linguistic choices. Yet, limited research has examined female agency through an approach that integrates systemic functional and critical discourse perspectives. This study aims to examine how female agency is discursively constructed in the song "Man I Need" by Olivia Dean through the integration of M. A. K. Halliday's (1994) Systemic Functional Linguistics (SFL) and Sara Mills' (1995) Feminist Critical Discourse Analysis, within Fairclough's (1995) three-dimensional CDA framework. Employing a descriptive qualitative research design, this study analyses 20 selected lines comprising 34 clauses, organized into three thematic groups based on their discursive functions. The findings reveal that the three SFL meta functions (ideational, interpersonal, and textual) converge to consistently position the female persona in the subject position, while the male partner is systematically placed in the object position across all thematic groups, giving rise to three analytically distinct forms of female agency. These findings demonstrate that female agency in this song is not merely a thematic message but a discursively constructed achievement, systematically produced through the language's own architecture.